Shifting The Customary Inheritance of The Minangkabau Tribe Based on The Perspective of Justice and Gender Equality - Vini Aprila D. Andra; Sonny Dewi Judiasih; Hazar Kusmayanti (Eduvest - Journal of Universal Studies, 2025)
The richness of Indonesian culture has an impact on the variation of regulatory systems that apply in each region, including the enactment of customary inheritance law for the Minangkabau Tribe. Modernity has an impact on the social adaptation of the community in addressing customary inheritance law. The research conducted examines the impact of injustice and gender inequality in Minangkabau customary inheritance law, as well as the shift in its provisions related to the principle of justice. The method used in the research is a normative juridical approach that focuses on exploring the interaction between customary inheritance law and positive law in the context of justice and gender equality. This qualitative approach research uses primary data through interviews and observations, as well as secondary data in the form of books, journals, and legal documents. The results of this study show that Minangkabau customary inheritance law which adheres to the matrilineal system gives the main role to women as heirs of high heirlooms. This reflects gender equality in Minangkabau society, where women are considered more capable of maintaining and caring for cultural and family heritage. However, over time, there has been a shift in gender roles, including men who have begun to become heirs influenced by migration and cultural acculturation. Nonetheless, the system still seeks to maintain a balance between customary traditions and the principles of Islamic law, which form the basis of inheritance distribution.